2020
DOI: 10.14444/7059
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Vitamin D in Spinal Surgery: Deficiency Screening, Treatment, and Outcomes

Abstract: In this review, we discuss the demonstrated value of vitamin D in bone maintenance, fracture resistance, spinal health, and spine surgery outcomes. Despite this, the effect of vitamin D levels in spine surgery has not been well described. Through this review of literature, several conclusions were drawn. First, despite the fact that a high number of spine surgery patients are vitamin D deficient, screening is not commonly performed. Second, adequate vitamin D levels will not be achieved in a majority of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…An animal model with rats after spinal fusion surgery revealed a dose dependent relationship between vitamin D supplements and fusion rate [28]. Several studies have also observed that higher 25(OH)VitD level was associated with the improvement of pain and function [21]. Waikakul et al reported that nine patients with failed back surgery syndrome had significantly improved pain and back function after vitamin D2 and vitamin D3 supplements for 6 months [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An animal model with rats after spinal fusion surgery revealed a dose dependent relationship between vitamin D supplements and fusion rate [28]. Several studies have also observed that higher 25(OH)VitD level was associated with the improvement of pain and function [21]. Waikakul et al reported that nine patients with failed back surgery syndrome had significantly improved pain and back function after vitamin D2 and vitamin D3 supplements for 6 months [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the inverse relationship of baseline 25(OH)VitD level with response to vitamin D supplements [32,33]. Therefore, if we consider to provide vitamin D supplements before spine surgery by a routine approach, it need to identify the patients who can benefit the most from vitamin D supplements and to determine the appropriate dosage of vitamin D supplements [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Although hypovitaminosis D is common in spinal fusion patients, the published prevalence varies greatly because evidence on 25(OH)D levels in spinal surgery is limited. 14 In posterolateral fusion (PLF), the interest in vitamin D deficiency as a risk factor stems from the relatively high rate of hypovitaminosis D and because 25(OH)D supplementation appears to be a quick, low-risk, highly reliable, and potentially cost-effective strategy at reducing pseudarthrosis rates after spinal fusion. 6,7,11,[14][15][16][17][18][19] This study investigated whether preoperative vitamin D supplementation can be used as a cost-effective mechanism to reduce postsurgical pseudarthrosis rates, clinical morbidity, and costly revision surgery for PLF patients.…”
Section: Introductionmentioning
confidence: 99%